EXPLORING EFFECTIVE METHODS IN PEDAGOGY: FOSTERING ENGAGING AND TRANSFORMATIVE LEARNING EXPERIENCES - Sadullayeva Nazokat Kuvondiq qizi (Zeta Repository, 2023)
This article provides an overview of effective methods in pedagogy, exploring various approaches to enhance teaching and learning experiences. It discusses traditional and innovative methods, such as lecture-based instruction, collaborative learning, experiential learning, the Socratic method, problem-based learning, differentiated instruction, and blended learning. The article emphasizes the importance of promoting engagement, critical thinking, and personalized learning to meet the diverse needs of students.